Optimization of the general acceptability though affective tests and response surface methodology of a dry cacao powder mixture based beverage - Chau Loo Kung, Elena (2013)
This research work had as main objective optimizing the general acceptability though affective tests and response surface methodology of a dry cacao powder mixture based beverage. We obtained formulations of mixtures of cacao powder with different concentrations of 15%, 17.5% and 20%, as well as lecithin concentrations of 0.1%; 0.3%; and 0.5% maintaining a constant content of sugar (25 %), Vanillin (1%) that included cacao powder with different pH values: natural (pH 5) and alkalinized (pH 6.5 and pH 8) and water by difference to 100%, generating a total of fifteen treatments to be evaluated, according to the Box-Behnen design for three factors. The treatments underwent satisfaction level tests to establish the general acceptability. The treatment that included cacao powder with a concentration of 17.5 %, pH 6.5 and lecithin concentration of 0.3 % obtained the best levels of acceptability. The software Statgraphics Plus 5.1 was used to obtain the treatment with maximum acceptability that corresponded to cacao powder with pH 6.81, with a concentration of 18.24 % and soy lecithin in 0.28% with a tendency to what was obtained in the satisfaction levels tests. Finally we characterized in a physical-chemistry and microbiological way the optimum formulation as well as evaluated sensitively obtaining an acceptability of 6.17.